Changes in bird assemblages in an afforestation landscape in the Lower Delta of the Paraná River, Argentina. (2nd October 2019) - Magnano, Andrea L.; Fracassi, Natalia G.; Nanni, Analía S.; Quintana, Rubén D.
ABSTRACT: Global loss of wetlands has increased significantly in recent years. As a result, many wetlands have experienced changes in biotic communities, including birds. We compare the temporal variation in bird communities and the effects of land-use change on the structure and function of avian assemblages in the Lower Delta of the Paraná River (Argentina). We detected 28 families and 80 species of birds, with the highest richness, diversity and evenness in spring and summer because of the arrival of migratory species. Bird diversity, richness and evenness were significantly higher in secondary forests than in poplar plantations and cattle-grazing grasslands. Bird assemblages were related to structural differences of the habitat types and only generalist forest species were found in active plantations. Secondary forests exhibited species typical of the original riparian forest, practically extinct in the region. We speculate that abundance of guilds among habitat types is related to food supply and to plant composition. Our study shows for the first time how the conversion of wetlands into a Salicaceae plantation impacts on birds, particularly on wetland species. This demonstrates the need to implement management strategies to maintain a mosaic including secondary forests and freshwater marshes in order to conserve these species.